2014
DOI: 10.1177/0022219414522708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Predictive Impact of an Emergent Literacy Model on Dyslexia in Italian Children

Abstract: The strong differences in manifestation, prevalence, and incidence in dyslexia across languages invite studies in specific writing systems. In particular, the question of the role played by emergent literacy in opaque and transparent writing systems remains a fraught one. This research project tested, through a 4-year prospective cohort study, an emergent literacy model for the analysis of the characteristics of future dyslexic children and normally reading peers in Italian, a transparent writing system. A coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 63 publications
(107 reference statements)
2
40
0
12
Order By: Relevance
“…Readers need to quickly coordinate these skills in an effortless manner (Fuchs et al, 2001). In fact, the capacity to coordinate phonological and orthographic representations of the word resulted to be predictive both, reading acquisition and reading impairment, even when assessed in kindergarten (Bigozzi, Tarchi, Pezzica, & Pinto, 2014). Yet, differences in orthographic depth between languages (English vs. transparent orthographies) also influence this reading parameter.…”
Section: Reading-spelling Relationship In Transparent Writing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers need to quickly coordinate these skills in an effortless manner (Fuchs et al, 2001). In fact, the capacity to coordinate phonological and orthographic representations of the word resulted to be predictive both, reading acquisition and reading impairment, even when assessed in kindergarten (Bigozzi, Tarchi, Pezzica, & Pinto, 2014). Yet, differences in orthographic depth between languages (English vs. transparent orthographies) also influence this reading parameter.…”
Section: Reading-spelling Relationship In Transparent Writing Systemsmentioning
confidence: 99%
“…That spelling results to be the common core between reading and writing confirms at the formal literacy level the existence of a common predictive core among emergent literacy skills. Past research has showed that kindergarteners' conceptual knowledge of the writing system, as assessed by an invented spelling task, predicts both, writing (Pinto, Bigozzi, Accorti Gamannossi, & Vezzani, 2009) and reading performances in primary school (Bigozzi et al, 2014), thus contributing to our knowledge on the similarities or differences in cognitive basis of reading and spelling. In a transparent writing system, children learn the sound to sign correspondences and how to process them fluently quite early, in first grade.…”
Section: Stability Of Reading and Writing Parameters At Two Points Inmentioning
confidence: 99%
“…For quite some time, phonological awareness had been considered to be the most important predictor of reading ( Paulesu et al, 2001 ) and spelling acquisition ( Babayiğit and Stainthorp, 2007 ; Vaessen and Blomert, 2013 ). Recently, however, several researchers have questioned its status in transparent orthographies, in both normal acquisition of reading and spelling ( Babayiğit and Stainthorp, 2007 ) on the one side, and in learning disorders ( Wimmer and Schurz, 2010 ; Bigozzi et al, 2016 ) on the other one. A better understanding of the role of phonological awareness in reading and writing thus requires the assessment of phonological awareness before the onset of formal literacy, since conventional acquisition of reading and writing exerts an autoregressive effect on phonological awareness ( Nikolopoulos et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…phonemic awareness) are the components of emergent literacy that are most predictive of children's later reading success (Lonigan, Schatschneider, & Westberg, ). It is now clear that early individual differences in emergent literacy can strongly predict both later reading achievement (Pinto, Bigozzi, Vezzani, & Tarchi, ; Scarborough, ; Snow, Burns, & Griffin, ; Wagner & Torgesen, ) and RD (Bigozzi, Tarchi, Pezzica, & Pinto, ; Elbro et al ., ; Pennington et al ., ; Pennington & Lefly, ; Snowling & Hulme, ).…”
mentioning
confidence: 99%